INTRODUCTION TO ENGLISH VOCABULARY THROUGH ANIMATION MEDIA - Lia Mudrikah, Ayu Fajarwati, Yusdiana (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
This research aims to explore vocabulary introduction methods for 5-6 year old children and to analyze the correlation between the use of Diva Series animation videos and English vocabulary acquisition at PAUD BKB KEMAS Al-Hidayah, Ciagel Village, Kibin District, Serang Regency). A descriptive qualitative research method was employed to study existing problems and periodic work procedures. Based on the research findings, it was discovered that several children at PAUD BKB KEMAS Al-Hidayah were able to pronounce some English vocabulary. They acquired this vocabulary through watching YouTube videos. Children who already knew English vocabulary appeared more confident. PAUD BKB KEMAS Al-Hidayah utilized animation media in learning activities for English vocabulary introduction, with the Diva Series animation being one of the primary choices. This animation was considered to have great potential as a learning tool for early childhood English language, helping children develop vocabulary in a fun and effective manner